A note on optimal 'riskless' and 'risk' prices for the newsvendor problem with an assembly cost. Issue 2 (8th February 2010) - Leng, Mingming; Parlar, Mahmut
For an assemble-to-order firm operating in a single period, we find that, for the multiplicative demand case the optimal riskless price may or may not be higher than the optimal risk price. However, for the additive demand case, the optimal riskless price is always greater than the optimal risk price. [Accepted: September 2009]